 Mathematics
16 May, 23:50

# Find m(-3x + 20)(-2x + 55)

0
1. 17 May, 01:35
0
Answer: Solution for (-3x+20) + (-2x+55) = 180 equation: x = - 21

Step-by-step explanation:

Simplifying

(-3x + 20) + (-2x + 55) = 180

Reorder the terms:

(20 + - 3x) + (-2x + 55) = 180

Remove parenthesis around (20 + - 3x)

20 + - 3x + (-2x + 55) = 180

Reorder the terms:

20 + - 3x + (55 + - 2x) = 180

Remove parenthesis around (55 + - 2x)

20 + - 3x + 55 + - 2x = 180

Reorder the terms:

20 + 55 + - 3x + - 2x = 180

Combine like terms: 20 + 55 = 75

75 + - 3x + - 2x = 180

Combine like terms: - 3x + - 2x = - 5x

75 + - 5x = 180

Solving

75 + - 5x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-75' to each side of the equation.

75 + - 75 + - 5x = 180 + - 75

Combine like terms: 75 + - 75 = 0

0 + - 5x = 180 + - 75

-5x = 180 + - 75

Combine like terms: 180 + - 75 = 105

-5x = 105

Divide each side by '-5'.

x = - 21

Simplifying

x = - 21